Pemikiran Ekonomi Islam Ibnu Miskawaih - Miftaakhul Amri; Siti Maghfiroh; Umdah Aulia Rohmah; Cahya Ningrum Ramadhani; Een Setiana; Muhammad Fairuz Abyan Rohimin (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This study aims to explore the Islamic economic thought articulated by Ibnu Miskawaih, a prominent Muslim philosopher of the 10th century. The urgency of this research lies in the need to understand the foundations of Islamic economics rooted in ethical and moral values. The research method employed is qualitative with a historical approach and content analysis. The theory used in the analysis is the virtue ethics theory espoused by Ibnu Miskawaih, emphasizing the importance of justice, balance, and happiness in economic life. The findings indicate that Ibnu Miskawaih's economic thought emphasizes fair wealth distribution, the avoidance of usury practices, and the role of the state in regulating the economy for the common good. The analysis and discussion compare these thoughts with conventional economic theories, finding alignment in basic principles but differences in practical applications. The conclusion of this research is that Ibnu Miskawaih's economic thought offers an ethical and sustainable alternative to modern economic systems, which often neglect moral aspects. This thought is relevant for further study in the context of contemporary Islamic economic development. Keywords: ibn miskawaih; islamic economics thought; virtue ethics; wealth distribution; suistainable economy.